Pengaruh Penggunaan Hijauan Rawa Fermentasi Terhadap Penampilan Kambing Kacang (Capra hircus) - Jaelani, A.; Rostini, T.; Zakir, M. I.; Jonathan, Jonathan (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
The study effect of using swamp forages fermentation to Kacang Goat performance wasconducted in Marabahan City from August till September 2013. This study was used an experimental method. The design used was a completely blocked design with 3 treatments and 4 Block as replications (3x4) to obtain 12 units. The Treatment are K1 (using 100% fresh forage), K2 (using silage of swamp forage), K3 (using haylage of swamp forage). The goat was average 11-14 kg body weight.ANOVA test results showed that using of swamp forages fermentation more significantly affect the feed consumption (570.8 g.goat-1.day-1), and significantly to final bodyweight (16.3 kg), but did not significantly affect to average daily gain, and feed convertion. Treatment Silage of forage swamp could be raise feed consumption and final body weight of Kacang goat.Key words: Swamp forage, silage, haylage, Kacang goat